Climate Resilience: Clarifying its Moral Foundations - Ostheimer, Jochen (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
In both discourses on resilience and climate, there is an emerging concept, namely climate resilience. This concept is examined from an ethical standpoint, with particular emphasis on its validity claims. A comparison with the more firmly entrenched concept of sustainability reveals that resilience is not a moral but a functional concept, thus lacking the capacity to provide a rationale for ethically sound political decisions on its own. The ambiguity of climate resilience is elucidated by revisiting the distinction between adaptation and mitigation, a common theme in climate policy. The argument is made that a transformative approach to climate resilience must be grounded in an open public debate on the good society